1986
DOI: 10.1159/000234112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drugs on the Increase in Cell Numbers in the Peritoneal Cavity of the Actively Sensitised Mouse after Intraperitoneal Challenge with Antigen

Abstract: The injection of antigen into the peritoneal cavity of actively sensitised mice produced an increase in the number of neutrophils in peritoneal washings collected 4 h later but after 1 day the numbers had returned to control levels. The increase in numbers of mononuclear cells and eosinophils in the peritoneal washings peaked at 2 days and persisted for at least 5 days. Dosing the mice with phenidone, a dual inhibitor of the cyclo-oxygenase and lipoxygenase pathways of arachidonic acid metabolism, potentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
2

Year Published

1988
1988
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
(2 reference statements)
1
8
2
Order By: Relevance
“…As suggested in animal (33)(34)(35) and human studies, allergen challenge induces strong leukocyte recruitment, as has been detected in tissue biopsies, (36 -38) although histamine alone cannot induce any extravasation (30,36,39). Previous results are in line with our data that histamine is sufficient to induce leukocyte rolling, but endogenous mediators other than histamine are likely to participate in the reduction in velocity of the rolling leukocytes and in the actual extravasation during the generation of acute allergen-induced inflammation (7).…”
Section: Discussionmentioning
confidence: 85%
“…As suggested in animal (33)(34)(35) and human studies, allergen challenge induces strong leukocyte recruitment, as has been detected in tissue biopsies, (36 -38) although histamine alone cannot induce any extravasation (30,36,39). Previous results are in line with our data that histamine is sufficient to induce leukocyte rolling, but endogenous mediators other than histamine are likely to participate in the reduction in velocity of the rolling leukocytes and in the actual extravasation during the generation of acute allergen-induced inflammation (7).…”
Section: Discussionmentioning
confidence: 85%
“…OVA challenge induced a dose‐ and time‐dependent neutrophil migration in immunized mice, which peaked 4 h after challenge and returned to basal levels after 24 h, when a significant eosinophil and mononuclear cell infiltrate was observed. Similar kinetics for cell infiltration induced by antigen challenge in immunized mice and other species have been described (Abe et al ., 1994; Klein et al ., 1995; Metzger et al ., 1996; Sharpe & Smith, 1979; Spicer et al ., 1985; 1986; Zuany‐Amorim et al ., 1993). We found that OVA‐induced neutrophil accumulation was dependent on endogenous release of LTB 4 and cytokines, since neutrophil recruitment was inhibited by MK 886, an LTB 4 synthesis inhibitor (five‐lipoxygenase activating protein (FLAP) inhibitor; Miller et al ., 1990), by CP 105,696, an LTB 4 receptor antagonist (Koch et al ., 1994), and by dexamethasone, a glucocorticoid that inhibits eicosanoid and cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the rat (19), guinea pig (6) and mouse (20) indicate that drugs such as ketotifen or cromoglycate may achieve inhibition irrespective of the stimulus used to induce eosinophil accumu lation. There are few clinical reports on the effect of anti-asthma drugs on eosinophils in asthma.…”
Section: Discussionmentioning
confidence: 99%